Study skills for science, engineering and technology students. - Maier, Pat, ....-; Barney, Anna, ....-; Price, Geraldine, ....- (Harlow : Pearson, 2009)
An accessible, student-friendly handbook that covers all of the essential study skills that will ensure that Science, Engineering or Technology students get the most out of their course. Effective Study Skillscovers all of the key skills areas that will have the most impact on success on any Science, Engineering & Technology course, including: Effectively managing your time and stress Getting the most out of lectures and tutorials Improving your revision skills and exam performance Developing structured problem solving skills & techniques Mastering critical thinking, argument and analysis Developing successful reading and note-taking strategies Essay and research report planning and technical writing techniques Working in groups and effective presentation of assignments and projects Solving mathematical problems Working in the laboratory Final year project research and writing Real-life examples, self-assessment exercises and end-of-chapter quizzes will help students to assess their current skills base, develop them further and learn how to apply them in work and study.